2021
DOI: 10.1038/s41380-021-01145-7
|View full text |Cite
|
Sign up to set email alerts
|

A novel murine model to study the impact of maternal depression and antidepressant treatment on biobehavioral functions in the offspring

Abstract: Antenatal psychopathology negatively affects obstetric outcomes and exerts long-term consequences on the offspring’s wellbeing and mental health. However, the precise mechanisms underlying these associations remain largely unknown. Here, we present a novel model system in mice that allows for experimental investigations into the effects of antenatal depression-like psychopathology and for evaluating the influence of maternal pharmacological treatments on long-term outcomes in the offspring. This model system i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
18
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(22 citation statements)
references
References 97 publications
4
18
0
Order By: Relevance
“…In addition, stress loading is often performed before pregnancy 18 , 25 because physical stress loading may be severe during pregnancy. A recent study showed that isolated mice exhibited increased depression-like behavior than group-housing mice 26 , supporting the notion that psychological stress can induce depression even without physical stress loading.…”
Section: Discussionmentioning
confidence: 74%
“…In addition, stress loading is often performed before pregnancy 18 , 25 because physical stress loading may be severe during pregnancy. A recent study showed that isolated mice exhibited increased depression-like behavior than group-housing mice 26 , supporting the notion that psychological stress can induce depression even without physical stress loading.…”
Section: Discussionmentioning
confidence: 74%
“…For example, Xie et al (2019) reported an ameliorating effect of Lactobacillus reuteri on depressive behavior and its correlation to serotonin, whose precursor, tryptophan can be metabolized by Kynu and Nampt into NAD. More importantly, Scarborough et al (2021) investigated the role of serotonin in the social isolation model using serotonin reuptake inhibitor, fluoxetine (FLX). They found that FLX treatment was effective to prevent anxiety-related behaviors both in the isolated generation (dams) and in their offspring.…”
Section: Discussionmentioning
confidence: 99%
“…Two prevailing methods of imposing social stress on laboratory housed rodents that are arguably most related to aspects of human social behavior, are the social isolation and social instability stress paradigm (Table 3). One study modeled maternal depression in mice by incorporating social isolation both before and during gestation; concomitantly with antidepressant use (fluoxetine) (Scarborough et al, 2021). The social isolation paradigm per se, is not what makes this study unique.…”
Section: Psychological Induction Of Miamentioning
confidence: 99%
“…Environmental perturbations during pregnancy that result in either acute or chronic instances of inflammation in the human condition have been shown to include, dietary composition, frequency of exercise, adequate sleep, socioeconomic status, stress, exposure to pollutants, and the gut microbiome (Han et al, 2021a). The all-inclusive contribution of these factors has yet to be explored in an MIA rodent model but at present, there are reports from those who have explored the role of the maternal microbiome (Kim et al, 2017;Lammert et al, 2018), social stress or social isolation rearing (Vallée et al, 1997;Scarborough et al, 2021) and a maternal highfat diet (Bordeleau et al, 2020) on the resulting molecular and/or behavioral alterations in developing offspring (the use of environmental gestational stress paradigms in rodents are extensively reviewed here: Brunton, 2013;Weinstock, 2017;Van den Bergh et al, 2020).…”
mentioning
confidence: 99%